John Locke's politics of moral consensus - Forster, Greg, 1973- (Cambridge University Press, 2005)
The aim of this highly original book is twofold: to explain the reconciliation of religion and politics in the work of John Locke, and to explore the relevance of that reconciliation for politics in our own time.